Perspective on Porous Piezoelectric Ceramics to Control Internal Stress - Xiang Zhou; Kechao Zhou; Dou Zhang; Chris Bowen; Qingping Wang; Junwen Zhong; Yan Zhang (Nanoenergy Advances, 2022)
Due to the unique electromechanical energy conversion capability of ferroelectric materials, they have been at the forefront of materials science for a variety of applications such as sensors, actuators and energy harvesting. Researchers have focused on exploring approaches to achieve improved ferroelectric performance, and to ensure that the available material systems are more environmentally friendly. This comprehensive review summarizes recent research progress on porous ceramics and highlights the variety of factors that are often ignored, namely the influence of porosity on the Curie temperature, and applications of porous ferroelectric materials with adjustable Curie temperature. Finally, the development trends and challenges of porous ferroelectric materials are discussed, aiming to provide new insights for the design and construction of ferroelectric materials.